2011
DOI: 10.1186/1746-1596-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tumor thrombotic microangiopathy induced by gastric carcinoma: Morphometric and immunohistochemical analysis of six autopsy cases

Abstract: BackgroundPulmonary tumor thrombotic microangiopathy (PTTM) has been known as a rare and serious cancer-related pulmonary complication. However, the pathogenesis and pathophysiology of this debilitating condition still remains obscure and no effective management was recommended. The present study aims to elucidate the pathophysiology of PTTM.MethodsAutopsy records were searched to extract cases of pulmonary tumor embolism induced by metastasis of gastric carcinoma in the Toho University Omori Medical Center fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 12 publications
1
79
1
1
Order By: Relevance
“…Macrophage-derived factors, such as interleukin-6 (IL-6), as implicated in PAH [20], may also contribute to the fibrointimal proliferation in PTTM. Tumour cell nests are also evident in pulmonary veins and lymphatics [9,10,18], with evidence for lymphatic tumour invasion (Fig. 1c).…”
Section: Pathogenesismentioning
confidence: 98%
See 2 more Smart Citations
“…Macrophage-derived factors, such as interleukin-6 (IL-6), as implicated in PAH [20], may also contribute to the fibrointimal proliferation in PTTM. Tumour cell nests are also evident in pulmonary veins and lymphatics [9,10,18], with evidence for lymphatic tumour invasion (Fig. 1c).…”
Section: Pathogenesismentioning
confidence: 98%
“…Most reported cases of PTTM have been described in Japan, which is likely to reflect the high prevalence of gastric carcinoma. PTTM occurs in 16-27% cases of gastric carcinoma [4,5,9], especially the mucinous, signet ring and poorly differentiated subtypes [3,5,9]. PTTM is less commonly associated with breast [10], bladder [11], ovarian clear cell [12], hepatocellular [13] and gallbladder carcinoma [14].…”
Section: Incidence/epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that tumour cells have the abilities to activate coagulation pathway and local thrombus formation and trigger fibroblastic intimal proliferation via production of cytokines such as tissue factor,2 vascular growth factor, or platelet‐derived growth factor 3. High VEGF expression associated with gastric cancer could explain the high incidence of PTTM.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has become clear from both earlier and more recent animal studies that formation of a fibrin(ogen) and platelets containing thrombus around circulating tumour cells is a critical step during the blood-borne phase of the metastatic cascade (1,27). Although direct in-vivo evidence for this hypothesis in cancer patients is still lacking, microscopic tumour emboli resembling a thrombotic microangiopathy may be detected on autopsy in patients with gastric or ovarian carcinomas (28)(29)(30)(31). Interestingly, immunohistochemistry in some of these patients revealed strong TF staining on tumour cells, suggesting that the expression of procoagulant activity was an important determinant for tumour cell embolization.…”
Section: Clots In Cancer Clinical Burden and Key Events In Metastasis?mentioning
confidence: 99%